2014
DOI: 10.1007/s10964-014-0160-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Age, Gender, Hopelessness, and Exposure to Violence on Sleep Disorder Symptoms and Daytime Sleepiness Among Adolescents in Impoverished Neighborhoods

Abstract: Although sleep problems are associated with negative outcomes among adolescents, studies have not focused on sleep disorder symptoms among adolescents living in impoverished neighborhoods and how sleep problems may be related to two factors common in those environments: hopelessness and exposure to violence. This study used data from the longitudinal Mobile Youth Survey (MYS; N = 11,838, 49% female, 93% African-American) to examine trajectories of sleep problems by age (10-18 years) among impoverished adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 139 publications
0
26
1
Order By: Relevance
“…These findings provide compelling support for the role of social-cognitive processes in understanding how violence exposure can impact sleep functioning. In another longitudinal study, Umlauf et al (2015) extended previous work with the Mobile Youth Survey (Umlauf et al 2011) by showing violence exposure and hopelessness to have independent and multiplicative effects on adolescent sleep trajectories, with trauma-exposed females at particular risk for subsequent sleep problems related to traumatic stress. These studies provide excellent examples of integrating the community context into models of adolescent sleep.…”
Section: Overview Of Special Issue Contributionsmentioning
confidence: 64%
See 1 more Smart Citation
“…These findings provide compelling support for the role of social-cognitive processes in understanding how violence exposure can impact sleep functioning. In another longitudinal study, Umlauf et al (2015) extended previous work with the Mobile Youth Survey (Umlauf et al 2011) by showing violence exposure and hopelessness to have independent and multiplicative effects on adolescent sleep trajectories, with trauma-exposed females at particular risk for subsequent sleep problems related to traumatic stress. These studies provide excellent examples of integrating the community context into models of adolescent sleep.…”
Section: Overview Of Special Issue Contributionsmentioning
confidence: 64%
“…Studies by Kliewer and Lepore (2015) and Umlauf et al (2015) draw our attention to ways in which exposure to violence can impact sleep functioning. Among 362 young adolescents (ages 11-14 years) who witnessed or experienced community violence, both victimization and witnessing violence were longitudinally correlated with sleep problems (Kliewer and Lepore 2015).…”
Section: Overview Of Special Issue Contributionsmentioning
confidence: 99%
“…These studies find that a range of sleep measures, including sleep quality, sleep duration, insomnia symptoms, and sleep latency, are adversely associated with living in neighborhoods that are characterized by disorder, low social cohesion, and low socioeconomic status. These patterns have been observed among adults [411], adolescents [12, 13], and, to a lesser extent, children [14]. …”
Section: Neighborhood Context and Sleepmentioning
confidence: 99%
“…A longitudinal survey of 11,838 adolescents (10-18 years old) found that hopelessness and exposure to violence produce negative independent and multiplicative impacts on adolescent sleep, particularly for females (Umlauf, Bolland, Bolland, Tomek, and Bolland 2015). To investigate how SES affects sleep habits in U.S. preschoolers, researchers assessed 3217 children (*3 years old) for the presence, time, and consistency of bedtime routines.…”
Section: Sleepmentioning
confidence: 99%